SAT0228 Apoptotic effect of blys on endothelial cells and endothelial progenitor cells is mediated by blys receptros and is reverted by belimumab. (15th June 2017) - Spinelli, FR; Barbati, C; Ceccarelli, F; Colasanti, T; Morello, F; Massaro, L; Orefice, V; Alessandri, C; Conti, F; Valesini, G
Abstract : Background: Circulating endothelial progenitor cells (EPCs) are surrogate markers of endothelial function. Several studies demonstrated a reduction and functional impairment of EPCs in patients with Systemic Lupus Erythematosus (SLE), partially accounting for endothelial dysfunction. In murine models of atherosclerosis, treatment with a B Lymphocyte Stimulator (BLyS) inhibitor slowed the progression and reduced the size of atherosclerotic plaque. Belimumab (BLM) is a human anti-BLyS monoclonal antibody approved for the treatment of SLE. Objectives: We aimed at evaluating the effect of BLyS inhibition on EPCs and endothelial cells both ex vivo – in SLE patients receiving BLM– and in vitro . Moreover we investigated the expression of receptors for BLyS on EPC and mature endothelial cell surface. Methods: We enrolled consecutive patients with SLE who were due to start BLM, without known cardiovascular disease and age and sex-matched healthy subjects. Peripheral blood mononuclear cells (PBMC) were isolated by Ficoll density-gradient centrifugation. Cells were incubated with anti-CD34 and anti-VEGF-R2/KDR monoclonal antibodies; acquisition was performed by flow cytometry: EPCs were defined as CD34/KDR double-positive cells. Recovered EPC isolated from healthy donors' PBMC were plated on dishes coated with human fibronectin. Apoptosis was investigated after 6, 12 and 24 hours of incubation with BLyS at different concentrations – 5, 20 and 100 ng/ml – and re-evaluated after 6 hours of co-incubation with BLM at 173 and 300 μg/ml. The same experiments were repeated with the human endothelial cell line EA.hy926. Finally, EPCs and EA.hy926 were incubated with monoclonal antibodies anti-B Activating Factor-Receptor (BAFF-R), B-cell maturation antigen (BCMA) and transmembrane activator and calcium modulator and cyclophilin ligand (CAML) interactor (TACI) and analysed by flow cytometry; the results were expressed as mean fluorescence intensity (MFI). Results: We treated with BLM 10 female patients (mean age 45.6±10.2 yrs, mean disease duration 17.8±10.8 yrs) with active disease (mean baseline SLEDAI 8.4±2.6). Number of EPCs was significantly lower in SLE patients than in NHS (p=0.005). After 4 weeks of BLM, mean EPC number increased from 0.013±0.016 to 0.021±0.016 (p=0.012 vs baseline; p=n.s. vs NHS). At week 12, EPC number did not significantly differ compared to week 4 nor to baseline. In vitro studies demonstrated that 20 ng/ml of BLyS induced apoptosis of EPC after 6 hours of incubation; this effect was reverted by the addiction of BLM. Similarly, after 6 hours of incubation with 20 ng/ml of BLyS we detected an increase in EA.hy926 apoptosis that was reverted by co-incubation BLM. Both EPCs and EA.hy926 expressed on their surface BAFF-R (MFI =3.8 and 1.5, respectively) and BCMA (MFI =1.25 and 1.15, respectively); EPCs also expressed TACI (MFI =1.4). Conclusions: The results of this study demonstrated that the reduction of EPCs number detected in SLE patients was restored by BLM. In vitro results support a direct pro-apoptotic effect of BLyS that was reverted by the addition of BLM both in EPCs and EA.hy926 culture. The apoptotic effect of BLyS seems to be mediated by the three receptors (BAFF-R, BCMA and TACI) that are expressed on EPCs and mature endothelial cells surface. Disclosure of Interest: None declared